When is tit-for-tat unbeatable? - Dürsch, Peter; Oechssler, Joerg; Schipper, Burkhard (International journal of game theory, 2014)
We characterize the class of symmetric two-player games in which tit-for-tat cannot be beaten even by very sophisticated opponents in a repeated game. It turns out to be the class of exact potential games. More generally, there is a class of simple imitation rules that includes tit-for-tat but also imitate-the-best and imitate-if-better. Every decision rule in this class is essentially unbeatable in exact potential games. Our results apply to many interesting games including all symmetric 2$$×
Published online: 7 March 2013
Gesehen am 09.10.2020